Rotational Stability After Implantation of an Aspheric Toric Monofocal IOL with a Double C-Loop Haptic Design in Normal and High Axial Lengths - Ang RET; Tañá-Rivero P; Pastor-Pascual F; Stodulka P; Slovak M; Tetz M; Fischinger I; Cazal J; Gessa M; Ibarz-Barberá M; Holland D; Groneberg T (Clinical Ophthalmology, 2025)
Robert Edward T Ang,1 Pedro Tañá-Rivero,2 Francisco Pastor-Pascual,3 Pavel Stodulka,4,5 Martin Slovak,4 Manfred Tetz,6 Isaak Fischinger,7 Jorge Cazal,8 María Gessa,9 Marta Ibarz-Barberá,10 Detlef Holland,11 Thomas Groneberg12 1Asian Eye Institute, Makati City, Philippines; 2Oftalvist, Alicante, Spain; 3Oftalvist, Valencia, Spain; 4GEMINI Eye Clinic, Zlin, Czech Republic; 5Third Faculty of Medicine, Charles University, Prague, Czech Republic; 6Berlin Eye Research Institute (BERI), Berlin, Germany; 7Berlin Eye Research Institute (BERI), Wittenberg, Germany; 8Miranza IMO Barcelona, Barcelona, Spain; 9Miranza Virgen de Luján, Sevilla, Spain; 10Oftalvist, Madrid, Spain; 11Augenzentrum ONE, Kiel, Germany; 12Augenzentrum Erding, Erding, GermanyCorrespondence: Robert Edward T Ang, Asian Eye Institute, 8th Floor PHINMA Plaza, Rockwell Center, Makati City, Philippines, Email angbobby@hotmail.comPurpose: This study focuses on the analysis of the rotational stability after implantation of a biconvex aspheric toric monofocal intraocular lens (IOL) with a double C-loop haptic-design in eyes with normal versus high axial lengths.Methods: This was a prospective comparative study including 150 eyes with corneal astigmatism (≥ 0.75D) implanted with the biconvex aspheric monofocal PODEYE toric IOL and assessed up to 1 year after surgery. From these 150 eyes, 81 and 69 eyes belonged to normal (≤ 23.9mm) and high (≥ 24mm) axial lengths, respectively. About 4– 6 and 11– 13 months postoperatively, refraction and rotational stability of the PODEYE toric IOL were evaluated to find possible differences among both groups.Results: At the last postoperative-visit, 74.07% of eyes were within ± 0.50D and 95.06% of eyes were within ± 1.00D of the target-refraction for the normal group and 92.75% and 100% for the high axial length group, respectively. For the normal group, 77.78% and 96.30% of eyes had a postoperative refractive cylinder of ≤ 0.50D and ≤ 1.00D, respectively; and for the high axial length group these percentages were 84.05% and 100%, respectively. About 81.84% of eyes in the normal and 94.20% of eyes in the high axial length group were < 5 degrees of the intended axis. The mean IOL rotation was 2.93 ± 2.48 degrees in the normal axial length group, and 2.17 ± 1.73 degrees in the high axial length group. Based on the mixed ANOVA results, there is no evidence of a significant difference in IOL rotation over time, nor is there evidence that axial length plays a statistically significant role in rotational stability between 4– 6 and 11– 13 months postsurgery. Both groups exhibited similar and stable rotation outcomes.Conclusion: Our results reveal that the biconvex aspheric monofocal PODEYE toric IOL with double C-loop haptic-design shows excellent rotational stability without significant differences between eyes with normal and high axial lengths.Keywords: astigmatism, rotation, stability, monofocal toric, double C-loop, intraocular lens